Suppressing lithium dendrites by coating MoS2 with different layer spacings: A multiscale simulation study. (23rd November 2021) - Huang, Kai; Du, Jianglong; Hu, Jiajie; Tao, Haolan; Yang, Jie; Su, Haiping; Lian, Cheng; Shang, Yazhuo; Liu, Honglai
Graphical abstract: Highlights: The growth of lithium dendrites on MoS2 with different layer spacings is studied. A continuum model shows that the layer spacing of 1 nm can enhance ion diffusion. The QDFT calculation shows that 0.75 nm is the most suitable interlayer distance. Lithium dendrites grow on 2H- MoS2 are difficult than those on 1T- MoS2 . Abstract: MoS2 coating is an effective way to suppress the growth of lithium dendrites, but the study of the layer spacing effect is still lacking. In this work, the diffusion and adsorption of lithium ions on the MoS2 were studied by multiscale simulations. The transport of lithium ions on the MoS2 was investigated by a continuum method, which shows that the smaller layer spacing of 1 nm can enhance the ion diffusion. The QDFT method was used to study the lithium ions transport on 1T- and 2H- MoS2 with layer spacing of 0.65 nm - 1.15 nm. Results indicate that lithium dendrites are more difficult to grow on 2H- MoS2 . For both types of MoS2, enlarged layer spacing can reduce lithium dendrites growth and 0.75 nm is the most suitable interlayer distance for MoS2 expanding. We hope our results can provide guidance to the synthesis of dendrite-free lithium metal batteries.